International Entrepreneurial Orientation: the Case of Wineries Participating in the Wines of Brazil Project (Journal of Business, Universidad del Pacífico (Lima, Peru), 2017)
The objective of this study was to analyze the international entrepreneurial orientation (IEO) of wine companies that participated in the Wines of Brazil project. This is an exploratory and descriptive study with a qualitative methodology. The design is a multiple-case study of 10 wineries affiliated with the Wines of Brazil project. Data were collected through the analysis of documents and fieldwork collected via semi-structured interviews. Data were analyzed using content analysis conducted with the aid of Atlas.ti software. The results revealed that the dimensions of IEO were present, and certain elements stood out: those of categories from the dimensions International Innovativeness and International Proactiveness. Certain disparities were observed in the International Risk-taking dimension, since some elements were present with greater frequency than others. The findings of this study suggest that new elements should be added to the analytical categories: global products, participation in clusters and industry-wide projects. These elements allow financial risk to be attenuated and allow marketing to achieve internationalization.